2011
DOI: 10.1007/s00213-011-2296-2
|View full text |Cite
|
Sign up to set email alerts
|

Acute nicotine increases both impulsive choice and behavioural disinhibition in rats

Abstract: Present findings support the hypothesis that heightened impulsivity in smokers may in part be a consequence of the direct acute effects of nicotine. As such, drug-induced changes in impulsivity may play a critical role in the transition to and maintenance of nicotine dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 107 publications
2
47
2
Order By: Relevance
“…However, it is unlikely that this short-lived improvement in performance accuracy was secondary to an increase in appetite. Firstly, because accuracy of performance in this task has been previously shown to be unaltered by increases in primary motivation (Kolokotroni et al 2011), and secondly, the current data indicate that nicotine-treated animals were slower to collect their food rewards than saline controls. The manifestation of anhedonia during withdrawal in the present study may have reduced the perceived value of the food reward which could, in turn, have decreased motivation to seek the reward.…”
Section: No-go Trials With Early Responsesmentioning
confidence: 45%
See 3 more Smart Citations
“…However, it is unlikely that this short-lived improvement in performance accuracy was secondary to an increase in appetite. Firstly, because accuracy of performance in this task has been previously shown to be unaltered by increases in primary motivation (Kolokotroni et al 2011), and secondly, the current data indicate that nicotine-treated animals were slower to collect their food rewards than saline controls. The manifestation of anhedonia during withdrawal in the present study may have reduced the perceived value of the food reward which could, in turn, have decreased motivation to seek the reward.…”
Section: No-go Trials With Early Responsesmentioning
confidence: 45%
“…In particular, the anorectic effects of nicotine cannot account for the findings as an increase in latency to collect reward was not observed. Furthermore, reductions in primary motivation through pre-feeding have been shown to have no effect on task performance accuracy (Kolokotroni et al 2011) and to even decrease premature responding (e.g. Bizarro and Stolerman 2003).…”
Section: Effects Of Chronic Nicotinementioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, a deficit of inhibitory control can promote a vulnerability to continued drug usage and likelihood to relapse (Pattij and Vanderschuren, 2008;Winstanley et al, 2010). Like many abused substances, nicotine will promote indices of impulsive action and choice in rodents (Popke et al, 2000;Kolokotroni et al, 2011). For example, nicotine increases anticipatory (premature) responding in the 5-CSRTT (Stolerman et al, 2000;, a measure of impulsive action, and conversely drug-naïve rats identified as 'impulsive' based on high premature response rates, subsequently showed enhanced motivation to selfadminister nicotine compared with their 'less impulsive' counterparts (Diergaarde et al, 2008).…”
Section: Discussionmentioning
confidence: 99%